Metatranscriptomic Insights Into the Response of River Biofilm Communities to Ionic and Nano-Zinc Oxide Exposures - Bergsveinson, Jordyn; Roy, Julie; Maynard, Christine; Sanschagrin, Sylvie; Freeman, Claire N.; Swerhone, George D. W.; Dynes, James J.; Tremblay, Julien; Greer, Charles W.; Korber, Darren R.; Lawrence, John R. (Frontiers in Microbiology, 2020)
Manufactured Zn oxide nanoparticle (ZnO-NP) are extensively used world-wide in personal care and industrial products and are important contaminants of aquatic environments. To understand the overall impact of ZnO-NP contamination on aquatic ecosystems, investigation of their toxicity on aquatic biofilms is of particular consequence, given biofilms are known sinks for NP contaminants. In order to assess alterations in the functional activity of river microbial biofilm communities as a result of environmentally-relevant ZnO-NP exposure, biofilms were exposed to ionic zinc salt or ZnOPs that were uncoated (hydrophilic), coated with silane (hydrophobic) or stearic acid (lipophilic), at a total concentration of 188 g l-1 Zn. ICP-MS analyses of biofilms indicated ZnO-NP concentrated in the biofilms, with hydrophilic, hydrophobic and lipophilic treatments reaching 0.310, 0.250, and 0.220 g Zn cm-2 of biofilm, respectively, while scanning transmission X-ray microspectroscopy (STXM) analyses of biofilms confirmed that Zn was extensively- and differentially-sorbed to biofilm material. Microbial community composition, based on taxonomic affiliation of mRNA sequences and enumeration of protozoan and micrometazoan, was not affected by these treatments, and the total transcriptional response of biofilms to all experimental exposures was not indicative of a global toxic-response, as cellular processes involved in general cell maintenance and housekeeping were abundantly transcribed. Transcripts related major biological processes, including photosynthesis, energy metabolism, nitrogen metabolism, lipid metabolism, membrane transport, antibiotic resistance and xenobiotic degradation, were differentially expressed in Zn-exposures relative to controls. Notably, transcripts involved in nitrogen fixation and photosynthesis were decreased in abundance in response to Zn-exposure, while transcripts related to lipid degradation and motility-chemotaxis were increased, suggesting a potential role of Zn in biofilm dissolution. ZnO-NP and ionic Zn exposures elicited generally overlapping transcriptional responses, however hydrophilic and hydrophobic ZnO-NPs induced a more distinct effect than that of lipophilic ZnO-NPs, which had an effect similar to that of low ionic Zn exposure. While the physical coating of ZnO-NP may not induce specific toxicity observable at a community level, alteration of ecologically important processes of photosynthesis and nitrogen cycling are an important potential consequence of exposure to ionic Zn and Zn oxides.